2019
DOI: 10.1093/jxb/erz130
|View full text |Cite
|
Sign up to set email alerts
|

Rice aquaporin PIP1;3 and harpin Hpa1 of bacterial blight pathogen cooperate in a type III effector translocation

Abstract: Varieties of Gram-negative bacterial pathogens infect their eukaryotic hosts by deploying the type III translocon to deliver effector proteins into the cytosol of eukaryotic cells in which effectors execute their pathological functions. The translocon is hypothetically assembled by bacterial translocators in association with the assumed receptors situated on eukaryotic plasma membranes. This hypothesis is partially verified in the present study with genetic, biochemical, and pathological evidence for the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 71 publications
(154 reference statements)
1
65
0
Order By: Relevance
“…To date, most research studies on harpins have focused on their biological activities [13,21,22]. For example, many studies have characterized harpin functional domains [3,12,23,24] and the roles of harpins in non-host plants [25][26][27]. Only a few research studies have assessed the thermal stability of harpins.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most research studies on harpins have focused on their biological activities [13,21,22]. For example, many studies have characterized harpin functional domains [3,12,23,24] and the roles of harpins in non-host plants [25][26][27]. Only a few research studies have assessed the thermal stability of harpins.…”
Section: Introductionmentioning
confidence: 99%
“…We have identified Hpa2, HrpF, and XopN as concomitant translocators of the Xoo TALE PthXo1, which was well studied with respect to its function in determining virulence of the standard Xoo strain PXO99 A on the susceptible variety Nipponbare (Yang et al, 2006;Wang et al, 2018;Bian et al, 2019;Li et al, 2019;Zhang et al, 2019b). Evidence that demonstrates the translocator role has been shown as quantitative changes of PthXo1 translocation in Nipponbare plants inoculated with the WT and genetically modified POX99 A strains in the presence and absence of Hpa2, HrpF, and XopN, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In the Cya reporter assay using rice leaves inoculated by the leaf-center-infiltrating method as did usually (Kvitko et al, 2007;Chakravarthy et al, 2017;Li et al, 2019), Hpa2, HrpF, and XopN were found to partake in PthXo1 translocation from PXO99 A -bacterial cells into the cytosol of Nipponbare cells. To initiate the assay, two elder leaves of 14-day-old Nipponbare seedlings were infiltrated with every bacterial suspension of pertinent Xoo strains.…”
Section: Hpa2 Hrpf and Xopn Are Concomitant Translocators Of Pthxo1mentioning
confidence: 92%
See 1 more Smart Citation
“…Pathogens deliver various effectors into plant host cells when pathogens attack plants. These effectors assist pathogen proliferation and suppress plant defense responses [ 95 , 96 , 97 , 98 , 99 , 100 , 101 ]. Two Pseudomonas effectors, HopR1 and HopBB1, has been suggested to be involved in psbD transcription by targeting PTF1 (PLASTID TRANSCRIPTION FACTOR 1), a transcription factor for psbD BLRP transcription [ 102 , 103 ].…”
Section: Chloroplast Gene Expression and Environmental Stressmentioning
confidence: 99%